A noção de relação na teoria linguística de Ferdinand de Saussure - Marques, Allana Cristina Moreira (2016)
Our work aims at investigating the notion of relation in Ferdinand de Saussure’s linguistic reflections. As we observe his theoretical production, we see this notion was amply worked in the elaboration of other concepts of his, for example, language, signe, value, arbitrariness, among others. However, beyond the capacity of the notion of relation to produce other concepts, the way it was conceived and the theoretical space it was placed allowed Saussure to break through the essentially historical-comparative studies of the epoch, what made a new way of thinking language to have its starting point. Taking it into account, firstly, by reading the work of Herman Paul, the one who represents the neogrammarians in our text, we examine in which way Saussure is distant from his contemporary linguistics when he distinguishes the linguistic relations and give them a new status in his investigation. Secondly, we study how the notion of relation has it own place in Saussure’s theoretical process of thinking the fundamentals which later would be considered the milestone for Modern Linguistics. For that, we analyse one of his manuscripts, Notes pour un livre sur la linguistique générale, and the Course in General Linguistics. The first is composed by sketches which would become a book, as Saussure promised in a letter to Meillet; and the latter contains the principals for the science of Linguistics. So we aim at researching how the notion of relation is treated in this corpus in order to see the way it is conceived both in the particular production of a manuscript written by Saussure itself and the book which was published and considered the turning point for Linguistics.